Kompabilitas Hukum bagi Pemegang Barang Gadai dalam Pasal 1150-1160 KUH Perdata dengan Hadits Riwayat Al-Tirmidzi - Bakhri, Zorya Kanoubie Attar; Tajul Arifin (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2024)
Pawning has become a financial instrument that is widely used by the public as a solution to get fast funds with goods as collateral. This article aims to examine the practice of pawning from a positive legal perspective in Indonesia, especially in the Civil Code, and compare it with the principles of pawning in Islam contained in the hadith. This research uses a normative and comparative juridical approach method with a focus on articles 1150-1160 of the Civil Code and authentic hadith narrated by Al-Tirmidhi. From the results of the analysis, both legal sources show harmony in the principles of pawning, with hadith as a moral and ethical guide, while the Civil Code provides a detailed legal framework regarding the rights and obligations of the parties involved. The harmony between these two sources of law confirms that the practice of pawning can function in harmony with sharia principles and applicable law. Therefore, it is important for parties involved in pawn transactions to understand and comply with the established rules, as well as uphold ethical and moral values in every transaction. It is hoped that this research can become a reference for practitioners, government and related institutions in maintaining integrity and fairness in pawn practices.